Philippine National Agricultural and Natural Resources Research System: Resource Allocation Issues and Directions for Reforms - Saturnina C. Halos; Cristina C. David; Eliseo R. Ponce; Corazon B. Lamug (Philippine Institute for Development Studies (PIDS), 1999)
The performance of the agriculture sector is a key determinant to the overall economic growth and to its people's food security. It continues to be a major source of GDP, Philippine total employment and livelihood of the rural sector. However, the sector has been performing poorly since 1980s. This is due to the underinvestment in the agricultural research system because agriculture technologies are not only subject to risks and uncertainties but are chaacterized by externalities, economies of scale/scope and long gestation periods. This study explores improvements in the allocation of public expenditures and institutional reforms meant to increase efficiency in the public agricultural research system. Rather than focusing at a project or disciplinary level, this study focuses on research allocation at a strategic level across commodity. In depth analysis shows that public sector support for agricultural research is necessary for promoting technological change in agriculture and the preservation of the sustainability of natural resources. In addition, research expenditures across commodities and regions have been highly incongruent to their relative economic importance measures in terms of gross value added contribution to commodity. Analysis of manpower profile indicates the need for strengthening of Department of Agriculture and Department of Environment and Natural Resources research agencies.
Keywords: 330; natural resources and environment; agriculture sector